Ionic conductivity studies on neodymium doped ceria in different atmospheres. (18th August 2010) - Bedekar, Vinila V.; Patra, Saheli; Dutta, Atanu; Basu, R.N.; , A.K. Tyagi
Nano-crystalline 10 and 20 mol% neodymium (Nd) doped ceria powders were prepared by gel-combustion synthesis. The single-phase nature of the nano powder has been confirmed by X-ray diffraction. These sinter-active nano powders resulted in dense products, as the sintered densities were found to be ∼90% of theoretical densities. Ionic conductivity studies were carried out in air, hydrogen and oxygen atmospheres. The samples showed ionic conductivity of 1.3 × 10−2 S cm−1 at 650°C, and the activation energy values obtained in this system were in the range of 0.7-1.0 eV. These studies also revealed that no electronic conduction was observed, as the ionic conductivity values were almost similar in different environments.